Early MR detection of experimentally induced cerebral ischemia using magnetic susceptibility contrast agents: comparison between gadopentetate dimeglumine and iron oxide particles. - Reith, Wolfgang; Forsting, Michael; Vogler, Hubert; Heiland, Sabine; Sartor, Klaus (American journal of neuroradiology, 1995)
PURPOSE To evaluate early patterns of MR changes in a rat model of cerebral ischemia using the first pass of two magnetic susceptibility contrast agents. - METHODS One hours after endovascular middle cerebral artery occlusion, all animals were examined in an experimental MR unit. After bolus application of gadopentetate dimeglumine and, 10 minutes later, of iron oxide particles, the MR changes of the first pass of these contrast agents were followed using a T2*-weighted fast low-angle shot sequence. Time-density curves of both contrast agents were analyzed and compared. - RESULTS After bolus injection of either (paramagnetic) gadopentetate dimeglumine or superparamagnetic particles, nonischemic brain parenchyma decreased markedly in signal, whereas the ischemic brain area remained relatively hyperintense (and thus became clearly delineated). Only after application of gadopentetate dimeglumine did a mild reduction in signal occur in the ischemic hemisphere, although the main artery was occluded. An explantation for this phenomenon might be residual capillary perfusion (plasma flow), which is detectable only when the smaller (paramagnetic) contrast molecules are being used. - CONCLUSIONS Cerebral perfusion deficits can be detected 1 hour after vascular occlusion with T2*-weighted fast low-angle shot sequences and bolus injection of paramagnetic or superparamagnetic MR contrast agents. Gadopentetate dimeglumine may be used as a marker of microcirculatory plasma flow.